Polar particle flux distribution and its spatial extent - Yakovchuk Olesya; Wissing Jan Maik (Journal of Space Weather and Space Climate, 2023)
Context: The main challenge in atmospheric ionisation modelling is that sparse measurements are used to derive a global precipitation pattern. Typically this requires intense interpolation or scaling of long-term average maps. In some regions however, the particle flux might be similar and a combination of these regions would not limit the results even though it would dramatically improve the spatial and temporal data coverage. Aims: The paper intends to statistically analyse the particle flux distribution close to the geomagnetic poles labelled as Polar Particle Flux Distribution (PPFD) and identify similar distributions in neighbouring bins. Those bins are grouped and the size of the PPFD area is estimated. The benefit is that single measurements within the PPFD area should be able to represent the particle flux for the whole area at a given time. Methods: We use spatially binned energetic particle flux distributions measured by POES and Metop spacecraft during 2001–2018 to identify a Kp-dependent area with a similar flux distribution as the one found close to the geomagnetic poles (|magn.lat| > 86°). First, the particle flux is mapped on a magnetic local time (MLT) vs. magnetic latitude grid. In the second step, the gridded data is split up according to Kp levels (forming the final bins). Third, the particle flux in every bin has been recalculated in order to replace zero-count rates with rates based on longer measurement periods which results in a more realistic low flux end of the particle distribution. Then the binned flux distributions are compared to the PPFD. A “Δ-test” indicates the similarity. A threshold for the Δ-test is defined using the standard deviation of Δ-test values inside the (|magn.lat| > 86°) area. Bins that meet the threshold are attributed as PPFD area. Results: PPFDs and the corresponding PPFD areas have been determined for all investigated particle channels, covering an energy range of 154 eV–300 keV for electrons and 154 eV–2.5 MeV for protons. Concerning low energy channels a gradual flux increase with rising Kp has been identified. High energy channels show a combination of background population and solar particle event (SPE) population that adds up with increasing Kp. The size of the PPFD area depends on particle species, energy and geomagnetic disturbance, as well as MLT. The main findings are: a) There are small but characteristic hemispheric differences. b) Only above a certain energy threshold do the PPFD areas increase with particle energy. c) A clear enlargement with rising Kp is identified – with exceptions for very low Kp. d) The centre of the PPFD area is shifted towards midnight and moves with Kp. Asymmetries of the boundaries could be explained by auroral intensity. e) For low-energy particles the main restriction of the PPFD area seems to be the auroral precipitation.